1969
DOI: 10.1080/00288306.1969.10420225
|View full text |Cite
|
Sign up to set email alerts
|

The Turbidite Problem

Abstract: The turbidity current hypothesis has met with much support as well as severe criticism. Dogmatic statements in support of this hypothesis are not uncommon in the literature and a clear distinction between fact and inference is not always made. First developed as an explanation for the origin of submarine canyons, the turbidity current hypothesis was later applied to explain the deposition of ancient flysch-type sediments as well as recent deep-sea deposits of alternating coarse and fine layers. Though a turbid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1972
1972
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…1969 to present). In contrast, sediment gravity flow deposits that occur in shallow water, such as in lakes or on delta fronts (not to be confused with delta fronts that extend into deep water), are uncommon, and no one has demonstrated that thick areally extensive sediment gravity flow deposits are forming today in shallow water, as suggested by Van der Lingen (1969). Thus, by comparison with the modern record, the very presence of voluminous sediment gravity flow successions in the geologic record is, in itself, strong evidence for deep-water deposition.…”
Section: Depositional Mechanismsmentioning
confidence: 99%
“…1969 to present). In contrast, sediment gravity flow deposits that occur in shallow water, such as in lakes or on delta fronts (not to be confused with delta fronts that extend into deep water), are uncommon, and no one has demonstrated that thick areally extensive sediment gravity flow deposits are forming today in shallow water, as suggested by Van der Lingen (1969). Thus, by comparison with the modern record, the very presence of voluminous sediment gravity flow successions in the geologic record is, in itself, strong evidence for deep-water deposition.…”
Section: Depositional Mechanismsmentioning
confidence: 99%
“…In areas I, II, and III discussed above, the Lower Silurian (Llandoverian and early Wenlockian) units are overlain conformably by a thin-bedded "flysch-type" on June 22, 2015 memoirs.gsapubs.org Downloaded from (Van Der Lingen, 1969) sequence, the Jemtland Formation (late Wenlockian-early Ludlovian) that is in turn overlain conformably by the "flysch-like" Fogelin Hill Formation (early Ludlovian-Siegenian(?)). These two formations are best exposed in the Stockholm Mountain syncline, a relatively simple structure that lies along the western margin of the Ashland synclinorium in the vicinity of Jemtland, Maine (area IV, Fig.…”
Section: Upper Silurian and Lower Devonian^) Lithofaciesmentioning
confidence: 99%
“…Kuenen (1964) divided the e division into e (turbidite mud) and e (pelagic/ t p hemipelagic mud) to distinguish between mud deposited by the turbidity current and the overlying mud deposited by pelagic and hemipelagic processes. Van der Lingen (1969) and Hesse (1975) used the letter e for turbidite mud and f for pelagic/ hemipelagic mud. Piper (1978) subdivided turbidite mud (e) into three structural divisions: e 1 (laminated mud), e 2 (graded mud) and e 3 (ungraded mud), and retained the f notation for overlying hemipelagic or pelagic sediment.…”
mentioning
confidence: 99%